Monitoring the Emergence of Algal Toxins in Shellfish: First Report on Detection of Brevetoxins in French Mediterranean Mussels - Zouher Amzil; Amélie Derrien; Aouregan Terre Terrillon; Audrey Duval; Coralie Connes; Françoise Marco-Miralles; Elisabeth Nézan; Kenneth Neil Mertens (Marine Drugs, 2021)
In France, four groups of lipophilic toxins are currently regulated: okadaic acid/dinophysistoxins, pectenotoxins, yessotoxins and azaspiracids. However, many other families of toxins exist, which can be emerging toxins. Emerging toxins include both toxins recently detected in a specific area of France but not regulated yet (e.g., cyclic imines, ovatoxins) or toxins only detected outside of France (e.g., brevetoxins). To anticipate the introduction to France of these emerging toxins, a monitoring program called EMERGTOX was set up along the French coasts in 2018. The single-laboratory validation of this approach was performed according to the NF V03-110 guidelines by building an accuracy profile. Our specific, reliable and sensitive approach allowed us to detect brevetoxins (BTX-2 and/or BTX-3) in addition to the lipophilic toxins already regulated in France. Brevetoxins were detected for the first time in French Mediterranean mussels (Diana Lagoon, Corsica) in autumn 2018, and regularly every year since during the same seasons (autumn, winter). The maximum content found was 345 µg (BTX-2 + BTX-3)/kg in mussel digestive glands in November 2020. None were detected in oysters sampled at the same site. In addition, a retroactive analysis of preserved mussels demonstrated the presence of BTX-3 in mussels from the same site sampled in November 2015. The detection of BTX could be related to the presence in situ at the same period of four Karenia species and two raphidophytes, which all could be potential producers of these toxins. Further investigations are necessary to understand the origin of these toxins.